Electrical Engineering and Applied Computing - Ao, Sio-Iong.; Gelman, Len.; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
This book includes fifty-five chapters, revised and extended from research articles originally presented at the World Congress on Engineering 2010. Topics covered include Control Engineering, Network Management, Wireless Networks, Biotechnology, Signal Processing, Computational Intelligence, Computational Statistics, Internet Computing, High Performance Computing, and industrial applications. The book offers the state of the art of tremendous advances in electrical engineering and applied computing and also serves as an excellent reference work for researchers and graduate students working on electrical engineering and applied computing. 0
1. Mathematical Modelling for Coal Fired Supercritical Power Plants and Model Parameter Identification Using Genetic Algorithms -- 2. Sequential State Computation Using Discrete Modeling -- 3. Detection and Location of Acoustic and Electrical Signals from Partial Discharges with an Adaptative Wavelet-filter Denoising -- 4. Study on a Wind Turbine in Hybrid Connection with an Energy Storage System -- 5. Sar Values in a Homogenous Human Head Model -- 6. Mitigation of Magnetic Field under Overhead Transmission Line -- 7. Universal Approach of the Modified Nodal Analysis for Nonlinear Lumped Circuits in Transient Behavior -- 8. Modified 1.28 TBIT/S (32 X 4 X 10 GBIT/S)Absolute Polar Duty Cycle Division Multiplexing-WDM Transmission over 320 KM Standard Single Mode Fiber -- 9. Wi-Fi WEP Point-to-Point Links: Performance Studies of IEEE 802.11 a,b,g Laboratory Links -- 10. Interaction between the Mobile Phone and Human Head of Various Sizes -- 11. A Medium Range GBPS FSO Link: Extended Performance Measures -- 12. A Multi-Classifier Approach for Wi-Fi-based Positioning System -- 13. Intensity Constrained Flat Kernel Image Filtering, A Scheme for Dual Domain Local Processing -- 14. Convolutive Blind Separation of Speech Mixtures Using Auditory-based Subband Model -- 15. Time Domain Features of Heart Sounds for Determining Mechanical Valve Thrombosis -- 16. On the Implementation of Dependable Real-Time Systems with Nonpreemptive EDF -- 17. Towards Linking Islands of Information within Construction Projects Utilizing RF Technologies -- 18. A Case Study Analysis of an E-Business Security Negotiations Support Tool -- 19. Smart Card Web Server -- 20. A Scalable Hardware Environment for Embedded Systems Education -- 21. Yield Enhancement with a Nobel Method in Design of Application-specific Networks on Chips -- 22. On-line Image Search Application Using Fast and Robust Color Indexing and Multi-thread Processing -- 23. Topological Mapping Using Vision and a Sparse Distributed Memory -- 24. A Novel Approach for Combining Genetic and Simulated Annealing Algorithms -- 25. Buyer Coalition Formation with Bundle of Items by Ant Colony Optimization -- 26. Coevolutionary Grammatical Evolution for Building Trading Algorithms -- 27. High Performance Computing Applied to the False Nearest Neighbors Method: Box-assisted and KD-Tree Approaches -- 28. Ethernet Based Implementation of a Periodic Real Time Distributed System -- 29. Preliminary Analysis of Flexible Pavement Performance Data Using Linear Mixed Effects Models -- 30. Chi-squared, Yule?s Q and Likelihood Ratios in Tabular Audiology Data -- 31. Optimising Order Splitting and Execution with Fuzzy Logic Momentum Analysis -- 32. The Determination of a Dynamic Cut-off Grade for the Mining Industry -- 33. Improved Prediction of Financial Market Cycles with Artificial Neural Network and Markov Regime Switching -- 34. Fund of Hedge Funds Portfolio Optimisation Using a Global Optimisation Algorithm -- 35. Increasing the Sensitivity of Variability EWMA Control Charts -- 36. Assessing Response?s Bias, Quality of Predictions, and Robustness in Multiresponse Problems -- 37. Inspection Policies in Service of Fatigued Aircraft Structures -- 38. Toxicokinetic Analysis of Asymptomatic Hazard Profile of Welding Fumes and Gases -- 39. Classification and Measurement of Efficiency and Congestion of Supply Chains -- 40. Comparison of Dry and Flood Turning in Terms of Dimensional Accuracy and Surface Finish of Turned Parts -- 41. Coordinated Control Methods of Waste Water Treatment Process -- 42. Identical Parallel-machine Scheduling and Worker Assignment Problem Using Genetic Algorithms to Minimize Makespan -- 43. Dimensional Accuracy Achievable in Wire-cut Electrical Discharge Machining -- 44. Nash Game-theoretic Model for Optimizing Pricing and Inventory Policies in a Three-level Supply Chain -- 45. Operating Schedule: Take Into Account Unexpected Events in Case of a Disaster -- 46. Dynamic Hoist Scheduling Problem on Real-life Electroplating Production Line -- 47. Effect of HAART on CTL Mediated Immune Cells: An Optimal Control Theoretic Approach -- 48. Design, Development and Validation of a Novel Mechanical Occlusion Device for Transcervical Sterilization -- 49. Investigation of Cell Adhesion, Contraction and Physical Restructuring on Shear Sensitive Liquid Crystals -- 50. On the Current Densities for the Electrical Impedance Equation -- 51. Modelling of Diseased Tissue Diffuse Reflectance and Extraction of Optical Properties -- 52. Vertical Incidence Increases Virulence in Pathogens: A Model Based Study -- 53. Chaotic Oscillations in Hodgkin-Huxley Neural Dynamics: Stimulus Reconstruction and Neural Dynamics Retrieval -- 54. Quantification of Similarity Using Amplitudes and Firing Times of a Hodgkin-Huxley Neural Response -- 55. Reduction of HIV Infection that Includes a Delay with Cure Rate During Long-term Treatment: A Mathematical Study.
Keywords: Electronic books; Engineering; Computer network architectures; Software engineering; Electronics; Electronics and Microelectronics, Instrumentation; Software Engineering/Programming and Operating Systems; Computer Systems Organization and Communication Networks